Quantitative and Reproductive Performance of Single and Triplet Births of Etawah Crossbreed Goats In Lombok Island - Abyadul Fitriyah; Ni Made Andry Kartika; Ria Harmayani; Yuni Mariani; Nefi Andriana Fajri; Isyaturriyadhah Isyaturriyadhah (Fakultas Pertanian Universitas Muara Bungo, 2023)
This study aims to select female goats that have the potential to give birth to triplets. The analysis was carried out in four EC goats with triplets consisting of 12 twins and four single births. FSH and LH hormones were analyzed using the ELISA method (LIA kit). The t-test results showed that the average body size of single-born EC goats was significantly different (P0.05) in body weight (BW), chest circumference (CC), hip height (HH), and hip width (HW). The size of BW, CC, HH and HW were larger in the triplet than in the single birth type, with a ratio of BW (40.83±10.10 vs. 37.20±4.67) kg, CC (84.00±3,46 vs. 78.05±4.24) cm, HH (72.70±3.21vs 67.50±3.12) cm and HW (17.74±2.09 vs. 11.16±2.12) cm. Furthermore, there was a significant difference (P≤0.05) between the ages of single-born EC goats, which was higher than that of triplets, namely 4.20±1.41 vs. 1.67±1.03 (months). This had a significant effect (P≤0.05) on the body size, especially on the BW, BL, BH and HH. EC goats with twin birth types had significantly higher FSH hormone levels than those with single births, namely FSH (3.41±0.08 vs1.37±0.08) mlU/ml. In contrast, the EC goat kids did not show a significant difference. Conclusion: Goats selection with the potential to give birth to triplets can be detected from hip size and FSH levels in their blood which correlate positively with body weight and chest circumference measurements.